Distribution patterns of organic pollutants and microbial processes in marine sediments across a gradient of anthropogenic impact. (November 2018) - Zoppini, A.; Ademollo, N.; Patrolecco, L.; Langone, L.; Lungarini, S.; Dellisanti, W.; Amalfitano, S.
Abstract: Marine sediments are part of the hydrological cycle and the ultimate storage compartment of land-derived organic matter, including pollutants. Since relevant microbially-driven processes occurring at benthic level may affect the quality of the overall aquatic system, the necessity for incorporating information about microbial communities functioning for ecosystem modelling is arising. The aim of this field study was to explore the links occurring between sediment contamination patterns by three selected class of organic pollutants (Polycyclic Aromatic Hydrocarbons, PAHs, Nonylphenols, NPs, Bisphenol A, BPA) and major microbial properties (Prokaryotic Biomass, PB; total living biomass, C-ATP; Prokaryotic C Production rate, PCP; Community Respiration rate, CR) across a gradient of anthropogenic pollution. Sediments were sampled from 34 sites selected along 700 km of the western coastline of the Adriatic Sea. Organic contamination was moderate (PAHs <830 ng g −1 ; NPs <350  ng g −1 ; BPA <38  ng g −1 ) and decreased southward. The amount of PAHs-associated carbon (C-PAHs) increased significantly with sediment organic carbon (OC), along with microbial functional rates. The negative relation between PCP/CR ratio and OC indicated the shift toward oxidative processes in response to organic pollution and potential toxicity, estimated as Toxic Equivalents (TEQs). Our outcomes showed that sediment organic contamination and benthic microbial processes can be intimately linked, with potential repercussions on CO2 emission rates and C-cycling within the detritus-based trophic web. Graphical abstract: Image 1 Highlights: Anthropogenic impact and sediment contamination followed a geographical distribution. Sediment OM composition influenced all properties of benthic microbial communities. Microbial processes shifted toward oxidative metabolism in C-enriched sediments. Organic pollutants affect C-cycle and CO2 output by increasing microbial respiration. Abstract : Our results highlighted the impact of organic pollutants on sediment microbial communities by assessing the detrimental effects on metabolic processes involved in the C-flux.